Pengaruh Kepemimpinan Profetik dan Kepuasan Kerja terhadap Perilaku Kewargaan Organisasi (PKO) pada Karyawan Yayasan Prof. Dr. H. Kadirun Yahya di Medan: The Influence of Prophetic Leadership and Job Satisfaction toward Organizational Citizenship Behavior (OCB) on Employees of Prof. Dr. H. Kadirun Yahya Foundation in Medan - Sherry Hadiyani; Abdhy Aulia Adnans; Ferry Novliadi; Fahmi Fahmi (Society, 2021)
This study aims to determine the influence of prophetic leadership and job satisfaction toward organizational citizenship behavior (OCB) on employees of Prof. Dr. H. Kadirun Yahya Foundation in Medan. The study used a survey model involving 64 employees of Prof. Dr. H. Kadirun Yahya Foundation in Medan. The data were analyzed using multiple linear regression. The results indicated that prophetic leadership and job satisfaction significantly positively influenced organizational citizenship behavior (OCB). The coefficient of the determinant (R²) of prophetic leadership and job satisfaction showed a value of 0.134, meaning that variation of organizational citizenship behavior is influenced by prophetic leadership and job satisfaction as much as 13.4%, and other factors influenced the rest.